Sustaining employee well-being in hierarchical work communities: The roles of capability bundles and digital innovation channels in Indonesian hotels - Amrullah, Romanda Annas; Arleiny, Arleiny; Imanto, Frenki; Moejiono, Moejiono; Prayitno, Prayitno (Privietlab, 2025)
This study examines how employee capabilities and technology-mediated channels shape well-being in hierarchical hotel contexts marked by coercive leadership. Drawing on Approach–Avoidance Motivation and Diffusion of Innovation, we theorize a resource-and-channels model in which (a) Exapro-a capability bundle combining professional experience and proactive personality-enhances employee well-being, and (b) electronic diffusion of innovation (e-DOI) strengthens the welfare returns to Exapro by providing safer, auditable pathways for idea sharing when face-to-face voice is risky. We test the model using a three-wave longitudinal design across 26 three- to five-star hotels in Central Java and the Special Region of Yogyakarta (Indonesia) with N = 100 employees concentrated in frontline, rotating-shift roles. Using PLS-SEM (SmartPLS 4), measurement properties met recommended thresholds. Results show that the direct effect of despotic leadership on well-being is not significant (H1 rejected) once resources and channels are modeled. By contrast, despotic leadership positively predicts Exapro (H2 supported), Exapro positively predicts well-being (H3 supported), and e-DOI positively moderates the Exapro → well-being link (H4 supported). The model explains a moderate share of variance in well-being (R² ≈ .52). The findings reframe leader–well-being debates by demonstrating a suppressed/contingent direct effect of despotism and highlighting that what employees can do (Exapro) and how they can safely make it visible (e-DOI) are pivotal for sustaining well-being. Practically, hotels should build experience-based scripts, select/develop for proactivity, and institutionalize digital codification of micro-innovations while strengthening leadership accountability.